Health and society. Contributions of Latin American Perspectives - Oliva López Arellano; Florencia Peña Saint Martin (Social Medicine Publication Group, 2006)
The paper deals with the history of Latin America and the development of sociology and social medicine thought it. It makes a balance of the emergence and contributions of this innovative thinking.